Microbiological and histopathological investigations of Vibrio alginolyticus infection in cobia Rachycentron canadum (Linnaeus, 1766) cultured in sea cage - Rameshkumar, P.; Kalidas, C.; Tamilmani, G.; Sakthivel, M.; Abdul Nazar, A. K.; Ashok Maharshi, V.; Srinivasa Rao, K; Gopakumar, G. (Indian Journal of Fisheries, 2013)
The occurrence of disease caused by Vibrio alginolyticus in sea cage farming of hatchery produced cobia juveniles is reported in this paper. The affected animals showed signs of surfacing, sluggish swimming and bilateral exophthalmia followed by acute mortality. The bacterial pathogen Vibrio alginolyticus was isolated from systemic lesions of infected moribund cobia fingerlings which was confirmed based on biochemical characteristics. Further the 16S ribosomal RNA of the isolate was amplified and BLAST analysis of the sequence confirmed that the pathogen is V. alginolyticus. h istologically, the liver of affected fish showed fatty change, the eyes revealed congestion as well as infiltration of polymorphoneuclear cells in the choroid layer and acute glomerulornephritis was observed in the kidney.